Analisis Dampak Partisipasi Masyarakat pada Perekonomian Keluarga di Kampung Wisata Batik Okra Surabaya - Ajeng Rana Amelia Nugraha; Rachmawati Novaria; Dida Rahmadanik (Universitas 17 Agustus 1945 Semarang, 2025)
Kampung Wisata Batik Okra Surabaya which is located in the central area of Surabaya, has a great opportunity to be developed into one of the leading tourist destination centers as well as a cultural education center. Tourists who visit can participate in the process of making written batik which is the main attraction. This research is descriptive with a qualitative approach with the theory of community participation by Marschall (2006) to analyze the impact of community participation on the family economy in Kampung Wisata Batik Okra Surabaya. The results obtained through the research found that the Kampung Wisata Batik Okra Surabaya has not been optimal in meeting one of the three main indicators in the success of community participation stated by Marschall, namely the ability of the community to be involved in the process. The researcher's suggestion is to give awards to residents who actively contribute so that participation becomes more sustainable and develop sustainable training programs such as digital marketing, packaging of tourism products, or the management of batik galleries that are more attractive for tourists to visit.